ABOUT THE SHAPE OF A CLOUDY DROP IN AN ELECTRIC FIELD - Musarbi Kilyanievich Makuashev (Наука. Инновации. Технологии)
The drop shape in an exterior homogeneous electric field is considered. The analysis is grounded on a requirement of the balance of forces, enclosed to a drop. As the drop shape closed its equation is written in spherical co-ordinates. This equation is solved by decomposition on degrees of small parameter.